Influence of Connectedness to Nature and Environmental Identity On Pro-Environmental Behaviour Among Youths (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study investigated the influence of connectedness to nature and environmental identity on pro-environmental behaviour among youths. Three instruments were used in this study, they are: Pro-environmental Behavior Scale (PEBS), Connectedness to Nature Scale (CNS), and Environmental Identity Scale. Two hundred undergraduates were selected using a Convenience Sampling method. Four hypotheses were tested using regression, independent T-test. Result showed that connectedness to nature β= .30, t= 4.40, p.05.  Findings of the study were discussed in line with extant literatures. It was concluded that connectedness to nature and environmental identity are positive integers to pro-environmental behaviours.